2005
DOI: 10.1002/ccd.20306
|View full text |Cite
|
Sign up to set email alerts
|

Submassive pulmonary embolism and paradoxical embolic stroke treated with percutaneous rheolytic thrombectomy and closure of the patent foramen ovale

Abstract: The presence of patent foramen ovale (PFO) in patients with large pulmonary emboli (PE) is associated with an increased risk of stroke and mortality. Many patients are ineligible to receive thrombolytic therapy. We present a patient with bilateral PE and cryptogenic stroke who was treated effectively with rheolytic thrombectomy with AngioJet, PFO closure with CardioSeal device, and placement of an inferior vena cava filter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Patients rarely present with a stroke and PE simultaneously due to paradoxical embolisation across a patent foramen ovale (PFO) 42 43. More frequently (1–10% of cases) patients may develop an acute PE following a stroke 44.…”
Section: Clinical Dilemmasmentioning
confidence: 99%
“…Patients rarely present with a stroke and PE simultaneously due to paradoxical embolisation across a patent foramen ovale (PFO) 42 43. More frequently (1–10% of cases) patients may develop an acute PE following a stroke 44.…”
Section: Clinical Dilemmasmentioning
confidence: 99%
“…Therefore, the general recommendation has been to avoid it. 8,9,11,12,14,[19][20][21][22][23][24] Most of the reported adverse events, such as renal failure, arrhythmias, cardiac events, and damage to the pulmonary arteries, are related to the thrombectomy mode. In this study, we used only the PPS mode as an adjunctive clot fragmentation technique enhanced by the delivery of lytics within the thrombus.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of Morbidity with Other Case Series of PMT Morbidity in the present study is lower than what has been reported in prior case series. A review of the literature published to date using the Angiojet system for PMT of massive PE reveals 83 patients 11–15,17–30 . In 22% of those patients (18 of 83) some form of bleeding complication was reported such as bleeding–not further specified, hemoptysis, or the need for transfusion (Table 3).…”
Section: Discussionmentioning
confidence: 99%